Magnetic shield sheet

By adopting a structure of a highly thermally stable resin layer and a thermosetting adhesive layer on the magnetic barrier sheet, the problem of poor thermal stability of the existing magnetic barrier sheet in a high temperature environment is solved, and effective protection of the magnetic layer and stability of the magnetic barrier sheet function are achieved.

JP2025062955APending Publication Date: 2025-04-15PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172367
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When used in high-temperature environments, the thermal stability of existing magnetic barrier sheets is poor, resulting in remelting of hot melt resin, damaging the protective performance of the magnetic layer, causing cracks and falls off of the magnetic layer, affecting the function of the magnetic barrier sheet.

Method used

A resin layer with high thermal stability and a thermosetting adhesive layer are used. By setting the first and second resin layers, the first and second thermosetting adhesive layers on both sides of the magnetic barrier sheet, and protecting them on both sides of the magnetic layer, ensuring that the magnetic layer is not damaged in a high temperature environment.

Benefits of technology

It effectively suppresses the performance degradation of the magnetic barrier sheet in high temperature environments, ensuring the integrity of the magnetic layer and the functional stability of the magnetic barrier sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062955000003
    Figure 2025062955000003
  • Figure 2025062955000004
    Figure 2025062955000004
  • Figure 2025062955000005
    Figure 2025062955000005
Patent Text Reader

Abstract

To provide a magnetic shield sheet in which deterioration of appearance and lowering of magnetic characteristics are suppressed, even for use under high temperature environment.SOLUTION: A magnetic shield sheet is a laminate having a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order, wherein the magnetic layer contains a magnetic body having a magnetostriction constant λ of 30 or less and has thickness of 8 μm to 25 μm, each of the first resin layer and the second resin layer contains a resin having a melting point or a sublimation point of 250°C or higher and has thickness of 1 μm to 24 μm, and each of the first adhesive layer and the second adhesive layer contains an adhesive having a melting point of 150°C or higher and has thickness of 1 μm to 10 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a magnetic shielding sheet. [Background technology]

[0002] A magnetic shield sheet that can be used as a magnetic shield or electromagnetic wave shield for electronic devices, etc., uses an amorphous material or a nanocrystalline material as a magnetic ribbon having excellent magnetic properties, i.e., a magnetic layer. A nanocrystalline material suitable for the magnetic layer can be obtained by quenching a molten metal having an alloy composition that can be adjusted to a nanocrystalline structure, such as Fe-Cu-Nb-(Si,B)-based, and forming it into a long body called an amorphous ribbon, and then adjusting it to a nanocrystalline structure by heat treatment. One example of a nanocrystalline material is a material in which at least 50% of the structure is made of fine crystal grains with an average crystal grain size of 100 nm or less.

[0003] The soft magnetic quenched alloy ribbon made of nanocrystalline material that has been subjected to heat treatment tends to become brittle and loses toughness compared to before the heat treatment. In particular, when the ribbon is crystallized by heat treatment to adjust it to a nanocrystalline structure, the tendency to become brittle becomes significant, and there is a problem that the ribbon easily breaks during handling. When using a nanocrystalline material for a magnetic shielding sheet, using an alloy ribbon in an embrittled state will cause cracks, chips, etc. when stress is applied during processing and use, impairing its performance as a magnetic layer. Therefore, a resin is usually applied to both sides of the soft magnetic alloy ribbon and used as a laminate. For this reason, a method has been proposed in which a thermoplastic resin layer is bonded to at least one surface of a magnetic layer to obtain a laminate (see Patent Document 1). Thermoplastic resins have good processability, and have the advantage that, for example, a protective layer for the magnetic layer can be easily formed by laminating a thermoplastic resin layer and a magnetic layer and heating them. In addition to thermoplastic resins, heat-welding adhesives, so-called hot melt adhesives, double-sided tapes, thermoplastic resin films with a single-sided adhesive layer, etc. are used to protect the magnetic layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-317769 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in recent years, the applications of magnetic shielding sheets have expanded, and, for example, in addition to suppressing magnetic field noise in electronic devices such as smartphones, tablet-type information terminals, and mobile phones, magnetic shielding sheets are now being used in electronic circuits in automobiles, etc. When used in automobiles, etc., it is desirable to use them in environments with higher temperatures, for example, environments of 100°C or higher, rather than the conventional temperature range of -10°C to +80°C. Conventionally, thermoplastic resins and thermoplastic adhesives that have been widely used from the viewpoint of processability and the like have low heat resistance, and when used at high temperatures, for example, at environmental temperatures of 100° C. or higher, the thermoplastic resin may remelt. When the resin remelts, problems occur such as the resin layer deforming and peeling off from the nanocrystalline material that is the magnetic layer, or the resin layer itself undergoing thermal deformation or thermal discoloration, which may reduce the protective performance of the resin layer for the magnetic layer made of nanocrystalline material, and defects such as cracks and falling off may occur in the magnetic layer, resulting in a decrease in the function as a magnetic shield.

[0006] An object of one embodiment of the present disclosure is to provide a magnetic shielding sheet in which deterioration of appearance and degradation of magnetic properties are suppressed even when used in a high-temperature environment. [Means for solving the problem]

[0007] Specific means for solving the above problems include the following aspects. <1> A laminate having a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order, the magnetic layer having a magnetostriction constant λ of 30×10 -6A magnetic shielding sheet comprising a magnetic layer having a thickness of 8 μm to 25 μm containing the following magnetic material, wherein the first resin layer and the second resin layer are each resin layers having a thickness of 1 μm to 24 μm containing a resin having a melting point or sublimation point of 250° C. or higher, and the first adhesive layer and the second adhesive layer are each adhesive layers having a thickness of 1 μm to 10 μm containing an adhesive having a melting point of 150° C. or higher.

[0008] <2> The magnetic layer is a long body having a width of 30 mm to 500 mm, the widths of the first resin layer, the first adhesive layer, the second adhesive layer, and the second resin layer are 300 mm or more, and a plurality of the magnetic layers are arranged in parallel in the longitudinal direction of the long body on the surface of the first adhesive layer opposite to the side having the first resin layer. <1> The magnetic shield sheet according to claim 1. <3> The total thickness of the laminate is 33 μm to 65 μm. <1> or <2> The magnetic shield sheet according to claim 1. <4> It is in a rolled form. <1> ~ <3> 13. A magnetic shielding sheet according to claim 12. <5> The laminate is punched into a desired shape to form a magnetic shield member. <1> ~ <4> 13. A magnetic shielding sheet according to claim 12.

[0009] <6> the first adhesive layer and the second adhesive layer contain a thermosetting adhesive, and in at least one of the first resin layer and the second resin layer, when an area change rate before and after heating at a temperature for curing the thermosetting adhesive is A%, and a thickness of the first resin layer and the second resin layer is B μm, the product of A and B is 30% μm or less; <1> ~ <5> 13. A magnetic shielding sheet according to claim 12. (Method of measuring area change rate) In accordance with JIS C 2151:2019 and ASTM DD1204, the resin film constituting the first resin layer and the second resin layer is cut into samples having a size of 100 mm x 100 mm. The obtained resin film sample is heated in a heat treatment furnace under the conditions of 200 ° C. x 10 min or 150 ° C. x 30 min depending on the curing temperature of the thermosetting adhesive, and the thermal shrinkage rate in the width direction and length direction of the resin film before and after heating is measured by the following method. The area is calculated by the product of the obtained width and length, and the area change rate is measured by the following formula (a). Area change rate (%) = absolute value of [area of ​​resin film before heating - area of ​​resin film after heating] / area of ​​resin film before heating Formula (a)

[0010] -Method for measuring heat shrinkage- (1) Measure the width and length of the test piece before heating. (2) The test piece is placed in a hot air circulating thermostatic chamber and suspended under a load for a time and temperature condition according to the material of the resin film. (3) After heating, the test piece is cooled to room temperature, and then the length of the test piece after heat treatment is measured at the same part of the test piece as that measured before heating. (4) Using the obtained value, calculate the thermal shrinkage rate according to the following formula (b). Heat shrinkage rate (dimensional change rate) (%) = 100 × (Lo-L) / Lo Formula (b) In formula (b), Lo represents the size of the test piece before the heat test, and L represents the size of the test piece after the heat treatment. In the above measurement method, "hanging under load" refers to a state in which a load is applied so that the resin film is suspended without being deformed, such as by rolling up, and the load can be adjusted appropriately depending on the material of the resin film. Effect of the Invention

[0011] According to one embodiment of the present disclosure, there is provided a magnetic shielding sheet in which deterioration of appearance and degradation of magnetic properties are suppressed even when used in a high-temperature environment. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic example of a magnetic shield sheet according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates an example of a conventional magnetic shield sheet. [Figure 3A] FIG. 3A is a schematic diagram showing an example of the magnetic shield sheet of the present disclosure. [Figure 3B] FIG. 3B is a schematic cross-sectional view showing an example of an overlapping portion of the magnetic layers taken along line AA of the magnetic shield sheet according to the present disclosure shown in FIG. 3A. [Figure 3C] FIG. 3C is a schematic cross-sectional view showing another example of the overlapping portion of the magnetic layers taken along line AA of the magnetic shield sheet according to the present disclosure shown in FIG. 3A. [Figure 4] FIG. 4 is a schematic diagram showing an example of a manufacturing apparatus suitable for manufacturing the magnetic shield sheet of the present disclosure. [Figure 5A] FIG. 5A is a partially enlarged photograph showing the appearance of the magnetic shield sheet of Example 1 after heat treatment. [Figure 5B] FIG. 5B is a partially enlarged photograph showing the appearance of the magnetic shield sheet of Comparative Example 1 after heat treatment. [Figure 6] FIG. 6 is a graph showing the relationship between the heating time and the magnetic permeability in a high-temperature storage test for the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1. [Figure 7] FIG. 7 is a graph showing the magnetic permeability of the magnetic shield sheet of Example 1 and the magnetic shield sheet of Comparative Example 1 at frequencies of 100 Hz and 10,000 Hz. [Figure 8] FIG. 8 is a graph showing the magnetic permeability of the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2 at frequencies of 100 Hz and 10,000 Hz. [Figure 9]FIG. 9 is a graph showing the relationship between the product of the thickness of the first resin layer and the area change rate of the resin layer before and after heat treatment, and the magnetic permeability of a laminate for a magnetic shield sheet having the same layer structure as in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments, and can be implemented with appropriate modifications within the scope of the object of the present disclosure.

[0014] When describing the embodiments of the present disclosure with reference to the drawings, the description of the same components and reference numerals in the drawings may be omitted. Components indicated by the same reference numerals in the drawings are the same components. The dimensional ratios in the drawings do not necessarily represent the actual dimensional ratios.

[0015] In the present disclosure, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the lower and upper limits, respectively. In the numerical ranges described in stages in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0016] In this disclosure, ordinal numbers (e.g., "first" and "second") are terms used to distinguish components, and do not limit the number of components or the priority of the components.

[0017] In the present disclosure, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.

[0018] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.

[0019] In the present disclosure, the magnetic shielding sheet has a sheet-like form. When the surface of the magnetic shielding sheet is rectangular, the short side is defined as the "width" and the long side is defined as the "length". When the magnetic shield sheet is wound into a roll, the winding direction is defined as the "length direction", and the direction perpendicular to the length direction is defined as the "width direction". When the magnetic layer, adhesive layer, and resin layer that make up the magnetic shield sheet have a ribbon-like shape in which the long side of the sheet is five or more times longer than the short side, the sheet is sometimes called a "long body."

[0020] The magnetic shielding sheet of the present disclosure is a laminate having, in this order, a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer, wherein the magnetic layer is a magnetic layer having a thickness of 8 μm to 25 μm and containing a magnetic material having a magnetostriction constant λ of 30 or less, the first resin layer and the second resin layer are each resin layers having a thickness of 1 μm to 24 μm and containing a resin having a melting point or sublimation point of 250° C. or more, and the first adhesive layer and the second adhesive layer are each adhesive layers having a thickness of 1 μm to 10 μm and containing an adhesive having a melting point of 150° C. or more. The magnetic shield sheet of the present disclosure has a laminate structure in which both sides of an alloy ribbon serving as a magnetic layer are protected with a resin layer via an adhesive. Here, the adhesive layer in contact with one surface of the magnetic layer is referred to as the first adhesive layer, and the layer adhering to the magnetic layer via the first adhesive layer is referred to as the first resin layer. Also, the adhesive layer in contact with the surface of the magnetic layer opposite to the surface having the first adhesive layer is referred to as the second adhesive layer, and the layer adhering to the magnetic layer via the second adhesive layer is referred to as the second resin layer.

[0021] The laminate constituting the magnetic shield sheet of the present disclosure will be described with reference to the drawings. Fig. 1 is a cross-sectional view showing a schematic example of a magnetic shield sheet according to the present disclosure. The magnetic shield sheet 10 shown in Fig. 1 includes a first resin layer 12, a first adhesive layer 14, a magnetic layer 16, a second adhesive layer 18, and a second resin layer 20, in this order. The first resin layer 12, the first adhesive layer 14, the second adhesive layer 18 and the second resin layer 20 protect the magnetic layer 16 containing the magnetic material from both sides, and even if the magnetic shielding sheet 10 is deformed, damage to the magnetic layer 16 and peeling from the first resin layer or the second resin layer are suppressed.

[0022] In the magnetic shield sheet of the present disclosure, the magnetic layer is a magnetic layer having a thickness of 8 μm to 25 μm, containing a magnetic material having a magnetostriction constant λ of 30 or less, the first resin layer and the second resin layer are resin layers having a thickness of 1 μm to 24 μm, containing a resin having a melting point or sublimation point of 250° C. or more, and the first adhesive layer and the second adhesive layer are adhesive layers having a thickness of 1 μm to 10 μm, containing an adhesive having a melting point of 150° C. or more. Therefore, for example, when the adhesive layer contains a thermosetting resin, even if the adhesive layer is heated and cured, deformation of the adhesive layer and the resin layer is suppressed, and undesired damage to the magnetic layer is suppressed. In detail, the resin layer and the resin component contained in the adhesive layer have good heat resistance, and the thickness of each layer is relatively thin, which is combined to produce the effects of the present disclosure. Each layer will be described in detail below.

[0023] In conventionally known magnetic shield sheets, a thermoplastic resin is generally used for the resin layer that is a protective layer for the magnetic layer, and the thickness of the resin layer often exceeds 30 μm, and is often around 50 μm. Fig. 2 is a cross-sectional view showing an example of a conventionally known magnetic shield sheet. The magnetic shield sheet 22 shown in Fig. 2 has a first resin layer 24, a first adhesive layer 26, a magnetic layer 28, a second adhesive layer 30, and a second resin layer 32 in this order, and the layer configuration is similar, but the first resin layer and the second resin layer are resin layers with a thickness of more than 30 μm containing thermoplastic polyethylene with a melting point of 100 ° C to 150 ° C, and the adhesive contained in the adhesive layer also contains a thermoplastic adhesive such as a hot melt adhesive, so that, for example, in a high temperature environment exceeding 100 ° C, there is a concern that the thermoplastic resin will remelt and the protective performance of the magnetic layer will decrease.

[0024] The magnetic shield sheet of the present disclosure is not particularly limited in its structure, except that it is a laminate having a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order. The magnetic layer does not necessarily have to be laminated over the entire surfaces of the first resin layer and the first adhesive layer in the magnetic shield sheet, and may be formed only in a localized region. In the region where the magnetic layer is not disposed, the first adhesive layer and the second adhesive layer may be directly bonded to each other. From the viewpoint of magnetic shielding properties, it is preferable that the magnetic layer forming regions are regularly arranged.

[0025] A preferred embodiment of the magnetic layer is a magnetic shielding sheet in which the magnetic layer is a long body having a width of 30 mm to 500 mm, the widths of the first resin layer, the first adhesive layer, the second adhesive layer, and the second resin layer are 300 mm or more, and the magnetic layer is arranged in parallel in the longitudinal direction of the long body on the side of the first adhesive layer opposite the side having the first resin layer.

[0026] 3A is a schematic diagram showing an example of a magnetic shield sheet in which a plurality of magnetic layers are arranged in parallel on the surface of a first resin layer and a first adhesive layer adjacent to the first resin layer. In order to clarify the structure, FIG. 3A shows the layer structure of magnetic shield sheet 40 with a side surface as a cross section. In the oblique view of the magnetic shield sheet 40 shown in Figure 3A, a second adhesive layer 18 and a second resin layer 20 are laminated on the side of the magnetic layer 16 opposite the side in contact with the first adhesive layer 14. Although this may not be visible depending on the thickness of the resin layer 20, etc., Figure 3A shows it as a see-through view in order to clarify the shape and position of the magnetic layer 16. The multiple magnetic layers 16 arranged in parallel are arranged with some overlap because there is a risk of electromagnetic waves passing through the gaps if there are gaps between adjacent magnetic layers 16. In the parallel magnetic layers 16, the upper magnetic layer is shown with a solid line, and the end of the magnetic layer arranged with an overlap below is shown with a dashed line. The arrow drawn adjacent to magnetic shielding sheet 40 in FIG. 3A indicates the longitudinal direction of magnetic shielding sheet 40.

[0027] FIG. 3B is a schematic cross-sectional view showing an example of a cross section of the magnetic shield sheet shown in FIG. 3A taken along line AA. In the cross section of the magnetic shield sheet 40 taken along line AA shown in Fig. 3B, i.e., in the cross section in the width direction, the magnetic layers 16 are formed overlapping in the width direction of the magnetic shield sheet 40 as shown in Fig. 3B. Fig. 3B shows an example in which the first adhesive layer 14 and the second adhesive layer 18 are formed thinner in the region where the magnetic layers 16 overlap than in the region where the magnetic layers 16 do not overlap, and the thickness of the entire magnetic shield sheet is almost uniform.

[0028] FIG. 3C is a schematic cross-sectional view showing another example of the cross section taken along line AA of the magnetic shield sheet shown in FIG. 3A, which is different from that shown in FIG. 3B. In the cross section of the magnetic shield sheet 40 taken along line AA shown in Fig. 3C, the magnetic layers 16 are formed overlapping in the width direction of the magnetic shield sheet 40 as shown in Fig. 3C, and in the embodiment shown in Fig. 3C, the first adhesive layer 14 and the second adhesive layer 18 are formed to have substantially the same thickness even in the region where the magnetic layers 16 overlap as in the region where the magnetic layers 16 do not overlap. In the above embodiment, the adhesiveness of the overlapping portion is the same as in the other regions, but the overall thickness of the magnetic shield sheet 40 is shown to be somewhat thicker in the overlapping portion of the magnetic layers 16 than in the other regions. The form of the overlapping portion of the magnetic layers is not limited to the above, and the overlapping width of the magnetic layers 16 and the thicknesses of the first adhesive layer 14 and the second adhesive layer 18 in the overlapping area of ​​the magnetic layers 16 can be changed as appropriate depending on the intended use of the magnetic shielding sheet.

[0029] When the magnetic layer of the elongated body is laminated onto a wider resin layer via an adhesive layer, the width of the magnetic layer of the elongated body can be 40 mm to 550 mm, preferably 35 mm to 520 mm, and more preferably 30 mm to 500 mm, from the standpoints of productivity and the magnetic blocking properties of the resulting magnetic shield sheet. When the magnetic layer of a long body is laminated onto a wider resin layer, from the standpoint of productivity, it is preferable that the width of the resin layer be at least three times, more preferably at least five times, and even more preferably at least ten times, the maximum width of the magnetic layer.

[0030] <<Layer structure of magnetic shield sheet>> Next, each layer of the magnetic shield sheet of the present disclosure will be described. As described above, the magnetic shield sheet of the present disclosure has a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order.

[0031] <First Resin Layer, Second Resin Layer> The first resin layer and the second resin layer function as protective layers for the magnetic layer. The first resin layer and the second resin layer are each a resin layer containing a resin with a melting point or sublimation point of 250° C. or higher and having a thickness of 1 μm to 24 μm. Examples of resins having a melting point or sublimation point of 250°C or higher include polyimide [melting point: none, heat resistant temperature: 400°C], polyphenylene sulfide (PPS) [melting point: 260°C to 270°C: weight deflection temperature: 1.8MPa], aramid resin, which is an aromatic polyamide resin [melting point: none (due to sublimation), heat resistant temperature: 400°C], and high heat resistant polyethylene terephthalate (high heat resistant PET) [melting point: unknown, heat resistant temperature: 250°C], and the like. From the viewpoints of heat resistance and dimensional stability, PPS and aramid resin are preferred.

[0032] The melting point or sublimation point of the resin contained in the first resin layer and the second resin layer (hereinafter also referred to as the specific resin) is 250° C. or higher, preferably 260° C. or higher, and more preferably 270° C. or higher, from the viewpoint of protecting the magnetic layer. There is no particular upper limit to the melting point or sublimation point of the specific resin, but from the viewpoint of processability, the melting point can be 300° C. or lower and the sublimation point can be 500° C. or lower. In the present disclosure, the melting point or sublimation point of the resin contained in the resin layer is a general literature value. The resins contained in the first resin layer and the second resin layer may be the same or different. From the standpoint of stability when formed into a laminate, however, it is preferable that the resins are the same, since the thermal behavior of the first resin layer and the second resin layer will be consistent.

[0033] The first resin layer and the second resin layer may contain, in addition to the specific resin, other known components within the range that does not impair the effect. Other components include organic solvents, surfactants, plasticizers, colorants, etc.

[0034] The thickness of the first resin layer and the second resin layer is in the range of 1 μm to 24 μm. If the thickness of each resin layer exceeds 24 μm, it becomes difficult to deform the laminate, which may hinder the arrangement of the obtained magnetic shield sheet along a curved or bent surface. If the thickness is less than 1 μm, the handling property when laminating the protective layer decreases, and the function of protecting the magnetic layer may not be sufficiently obtained. By having the thickness of each resin layer in the above range, the protection property of the magnetic layer and the suppression of magnetic deformation due to thermal deformation of the magnetic shield sheet are improved. From the viewpoint of protecting the magnetic layer, the thickness of each resin layer is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more. The upper limit of the thickness of the resin layer is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less, from the viewpoints of the flexibility of the magnetic shield sheet and the dimensional stability during heating.

[0035] The thickness of the resin layer can be measured by a contact type film thickness meter. In the present disclosure, the thickness is measured at five points on the magnetic shield sheet, and the arithmetic average of the thicknesses obtained is regarded as the thickness of the resin layer. The thickness of each layer of the laminate constituting the magnetic shield sheet of the present disclosure, such as a resin layer and an adhesive layer, which will be described later, can also be measured in a similar manner. In addition, when measuring the thickness of each layer constituting a magnetic shielding sheet that already has a laminated structure, the thickness of each layer can be measured by observing a cut surface obtained by cutting the magnetic shielding sheet perpendicular to its surface.

[0036] <First adhesive layer, second adhesive layer> The first adhesive layer and the second adhesive layer are located between the resin layer serving as a protective layer for the magnetic layer and the magnetic layer described below, and have the function of bonding the first resin layer and the second resin layer to the magnetic layer. The first adhesive layer and the second adhesive layer each contain an adhesive agent having a melting point of 150° C. or higher and have a thickness of 1 μm to 10 μm.

[0037] The melting point of the adhesive (hereinafter also referred to as the specific adhesive) contained in the first adhesive layer and the second adhesive layer is 150°C or higher, preferably 160°C or higher, and more preferably 170°C or higher. The specific adhesive is preferably a thermosetting adhesive from the viewpoint of heat resistance and dimensional stability. Examples of the thermosetting adhesive include thermosetting adhesives containing a thermosetting resin selected from epoxy resin, unsaturated polyester resin (SMC: Sheet Molding Compound, BMC: Bulk Molding Compound, etc.), urea resin, diallyl phthalate resin, silicon resin, polyimide, and polyurethane, and among them, epoxy resin-based adhesives are preferred from the viewpoint of ease of adhesive layer formation and heat resistance of the obtained adhesive layer. The adhesive layer can also be formed by transferring a resin molded into a sheet shape. For example, the epoxy resin-based adhesive can be molded into a sheet shape and an adhesive layer can be formed by transferring to easily form an adhesive layer of uniform thickness. A one-component curing type epoxy resin adhesive cures when heated at 150° C. to 200° C., and has better heat resistance after curing than a two-component type epoxy resin adhesive. The resin contained in the first resin layer and the resin contained in the second resin layer may be the same or different from each other. From the viewpoint of stability when formed into a laminate, it is preferable that the resin contained in the first resin layer and the resin contained in the second resin layer are the same resin because the thermal behavior of the first resin layer and the second resin layer coincide and deformation due to thermal stress can be suppressed.

[0038] The first adhesive layer and the second adhesive layer each have a thickness of 1 μm to 10 μm. From the viewpoint of ensuring adhesion between the resin layer and the magnetic layer, the thickness of the adhesive layer is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 4 μm or more. From the viewpoint of suppressing size variation due to heating, the thickness of the adhesive layer must be 10 μm or less, can be 9 μm or less, and may be 8 μm or less. For example, when an epoxy resin adhesive is used, a thickness of the adhesive layer of about 10 μm can achieve a high level of both adhesiveness and dimensional stability against thermal behavior.

[0039] <Magnetic layer> The magnetic layer in the magnetic shield sheet of the present disclosure has a magnetostriction constant λ of 30×10 ―6 The magnetic layer is 8 μm to 24 μm thick and contains the following magnetic materials. The magnetic material contained in the magnetic layer has a magnetostriction constant λ of 30×10 ―6 As long as the magnetic material satisfies the following conditions, either an amorphous material or a nanocrystalline material can be used.

[0040] From the viewpoint of magnetic properties and strength, the thickness of the magnetic layer is in the range of 8 μm to 25 μm, preferably in the range of 10 μm to 20 μm, and more preferably in the range of 12 μm to 18 μm. The magnetostriction constant λ of the magnetic material used in the magnetic layer may be a literature value or may be measured by the following method.

[0041] <Method for measuring the magnetostriction constant λ of a magnetic material> The magnetostriction constant λ can be measured using a strain sensor. As the strain sensor, a strain sensor (model: SKF-40029) manufactured by Kyowa Electric Industries Co., Ltd. can be used. A strain sensor is attached to the magnetic layer with an adhesive. The adhesive used was Kyowa Electric Industry Co., Ltd.'s room temperature curing instant adhesive CC-33A. The adhesive was dropped in the direction of the roll rotation of the magnetic material (i.e., the longitudinal direction) or in the perpendicular direction (i.e., the width direction) and spread using finger pressure to adhere to the free surface of the adhesive application area. The obtained laminate of the magnetic material, adhesive, and sensor is measured using a strain amplifier (model: PCD-300A) manufactured by Kyowa Electronics Co., Ltd. as a strain amplifier. The size of the magnetic sample is 10 mm×10 mm, and the laminate is fixed to the center of an electromagnet of a measuring device using a jig. Measurements are performed by applying a magnetic field with a strength of approximately 5700 Oe to the magnetic material.

[0042] A nanocrystalline material suitable for the magnetic layer can be obtained by quenching a molten metal having an alloy composition that can be adjusted to a nanocrystalline structure, such as Fe-Cu-Nb-(Si,B), forming it into a long body called an amorphous ribbon, and then adjusting it to a nanocrystalline structure by heat treatment. One example of the nanocrystalline material is a material in which at least 50% of the structure is made up of fine crystal grains with an average crystal grain size of 100 nm or less. Nanocrystalline materials can be obtained by producing an amorphous ribbon and then heat treating it at a temperature above the crystallization temperature to microcrystallize it. The obtained amorphous alloy or nanocrystalline alloy magnetic ribbons as a magnetic layer can be used by partially overlapping the ends of the magnetic material so as to be magnetically and electrically coupled, and arranging multiple strips in parallel as shown in Figure 3A described above.

[0043] The total thickness of the laminate having the first resin layer, the first adhesive layer, the magnetic layer, the second adhesive layer, and the second resin layer in this order is preferably in the range of 33 μm to 65 μm, more preferably in the range of 35 μm to 62 μm, and even more preferably in the range of 40 μm to 60 μm. When the total thickness of the laminate is within the above range, the magnetic shielding sheet of the present disclosure has good flexibility and processability, and exhibits sufficient strength for practical use.

[0044] <Embodiments of magnetic shield sheet> There are no particular limitations on the embodiment of the magnetic shield sheet of the present disclosure. The magnetic shielding sheet of the present disclosure may be continuous in the longitudinal direction, or may be a sheet of any shape, such as a single independent rectangular sheet, or may be a magnetic shielding member obtained by punching a rectangular sheet or a continuously formed sheet into any shape. The magnetic shielding sheet of the present disclosure may be a wound roll-shaped magnetic shielding sheet. By winding up the laminate into a roll of magnetic shielding sheet, storage and transportation become easy, and the sheet can be unwound and used as needed. The magnetic shielding sheet is stored in a rolled form and unwound as required. It can be cut to an appropriate size for use, or can be subjected to punching processing. Moreover, the magnetic shield sheet of the present disclosure may be a magnetic shield member obtained by punching the above-mentioned laminate into a desired shape. By punching the laminate, a magnetic shield member of any desired shape can be obtained from the magnetic shield sheet, which can be easily incorporated into various devices. Magnetic shield members punched into a desired shape can be used, for example, as noise suppression devices for cameras, medical equipment with image processing, and the like.

[0045] <Preferable physical properties of magnetic shielding sheet> The first adhesive layer and the second adhesive layer include a thermosetting adhesive. When the area change rate of the first resin layer before and after heating to the temperature at which the thermosetting adhesive is hardened is A% and the thickness of the first resin layer is B μm, it is preferable that the product of A and B is 30% μm or less. The second resin layer also preferably has similar physical properties to the first resin layer. The rate of change in area before and after heating at a temperature at which the thermosetting adhesive is cured is measured by the following method.

[0046] (Method of measuring area change rate) In accordance with JIS C 2151:2019 and ASTM DD1204, a sample of 100 mm x 100 mm is prepared by cutting the resin film constituting the first resin layer, and the obtained resin film sample is heated in a heat treatment furnace under conditions of 200 ° C x 10 min or 150 ° C x 30 min depending on the curing temperature of the thermosetting adhesive, and the thermal shrinkage rate in the width direction and length direction of the resin film before and after heating is measured by the following method, the area is calculated by the product of the obtained width and length, and the area change rate is measured by the following formula (a). The second resin layer is also measured under the same conditions as those for the first resin layer. Area change rate (%) = [area of ​​resin film before heating - area of ​​resin film after heating] / area of ​​resin film before heating Formula (a)

[0047] -Method for measuring heat shrinkage- (1) Measure the width and length of the test piece before heating. (2) The test piece is placed in a hot air circulating thermostatic chamber and suspended under a load for a time and temperature condition according to the material of the resin film. Here, as described above, the load may be appropriately selected depending on the conditions under which the resin film is suspended in a state in which deformation of the resin film is suppressed. (3) After heating, the test piece is cooled to room temperature, and then the width and length dimensions of the test piece after heat treatment are measured at the same parts as those of the test piece before heating that were previously measured. (4) Using the obtained value, calculate the thermal shrinkage rate according to the following formula (b). Heat shrinkage rate (dimensional change rate) (%) = 100 × (Lo-L) / Lo Formula (b) In formula (b), Lo represents the size of the test piece before the heat test, and L represents the size of the test piece after the heat treatment. For example, when the thermosetting adhesive is aramid, the adhesive is heated at 200° C. for 10 minutes, whereas when the adhesive is another thermosetting adhesive, such as epoxy resin, the adhesive is heated at 150° C. for 30 minutes.

[0048] According to the inventors' research, it was found that while the heat resistance of the resin contained in the resin layer and adhesive layer is important for the stability of the magnetic permeability of the magnetic shielding sheet, in addition, the dimensional stability of each resin layer and each adhesive layer against thermal conditions such as heating and cooling is also important, and that in addition to the type of resin, the thickness of each layer also has an effect. When the product of the area change rate before and after heating of the first resin layer and the second resin layer and the thickness of the first resin layer and the second resin layer is 30%·μm or less by the above measurement method, undesired deformation of the magnetic layer before and after heating in the magnetic shield sheet is effectively suppressed. Note that the thickness of the first resin layer and the second resin layer refers to the thickness of each single resin layer of the first resin layer and the second resin layer.

[0049] <Method of manufacturing magnetic shield sheet> The magnetic shield sheet can be manufactured by a known method. The magnetic shield sheet of the present disclosure can be manufactured, for example, by the manufacturing method and manufacturing apparatus described in JP-A-2007-43077.

[0050] FIG. 4 is a perspective view showing an example of a main part of a manufacturing apparatus capable of manufacturing the magnetic shield sheet of the present disclosure. The manufacturing apparatus shown in FIG. 4 mainly comprises a heat roll 2, resin rolls 1a, 1b for transporting the resin layer, and thin coils 3a, 3b for transporting the magnetic layer, which are arranged around the heat roll 2. The manufacturing apparatus further mainly comprises compression rolls 8a, 8b, 8c for compressing the magnetic layer and the resin layer, and a roll 5 for winding up the laminated magnetic shield sheet. In FIG. 4, all rotation axes are arranged parallel to one another.

[0051] In Fig. 4, a resin film 6a that will become the first resin layer is unwound from a resin roll 1a toward a heat roll 2. An adhesive that will form an adhesive layer is applied to one side of the resin film. The amorphous alloy ribbons 7a and 7b forming the magnetic layer are formed on the resin film 6a having an uncured adhesive layer on one side thereof from the ribbon coils 3a and 3b at the same speed as the resin film, at a rate of, for example, 3.0×10 per unit cross-sectional area. 6 ~1.2×10 7 The film is unwound with a tension of 100 Pa and placed parallel to the heat roll 2. In addition, the amorphous alloy ribbon forming the magnetic layer may be pulled out from a winding roll arranged in multiple staggered stages so as to be magnetically and electrically coupled, and the amorphous alloy ribbon may be pulled out so that all of the contact surfaces with the heat roll for heating face one side, and the ends may be arranged in parallel with each other so as to overlap. The amorphous alloy ribbon is drawn out from each roll at the same speed and brought into contact with the circumference of the heat roll 2, and then immediately pressure-bonded to the resin film 6a having an adhesive layer by pressure-bonding rolls 8a and 8b. More precisely, for example, the amorphous alloy ribbons 7a may be pressed onto a resin film with a predetermined interval therebetween, and then immediately pressed by a pressing roll 8a, and thereafter, the portions not covered by the amorphous alloy ribbons 7a may be covered with the amorphous alloy ribbons 7b, and then immediately pressed by the pressing roll 8b. The amorphous alloy ribbon is brought into contact with the resin film and is pressed by a heat roll and a pressing roll.

[0052] Next, a resin film 6b forming a second resin layer is unwound from a resin roll 1b on the surface covered with the amorphous alloy ribbons 7a and 7b. An adhesive constituting a second adhesive layer is applied to the resin film 6b. The resin film 6b is pressed onto the amorphous alloy ribbons 7a and 7b by a pressing roll 8c to produce a magnetic shield sheet shielding material 9 which is a laminate of the resin film 6a forming the first resin layer and the first adhesive layer, the amorphous alloy ribbons 7a and 7b as the magnetic layer, and the resin film 6b forming the second adhesive layer and the second resin layer. The obtained magnetic shield sheet may be wound around a core material so that the direction of curvature of the amorphous alloy ribbon in the first roll is the same as that of the first roll, to obtain a magnetic shield sheet roll. The magnetic shield sheet may be transported after being wound around the roll 5, or may be cut into rectangular sheets without being wound around the roll 5, and the sheets may be stacked for storage and transport.

[0053] When the adhesive layer contains a thermosetting adhesive, after the formation of the laminate, and before winding or cutting, a step of curing the adhesive layer by heat treatment may be carried out.

[0054] Since the magnetic shielding sheet of the present disclosure has the above-mentioned configuration, the magnetic layer is effectively protected and undesired deterioration of the magnetic layer due to heat treatment is suppressed. In addition, the magnetic shielding sheet of the present disclosure has an AC relative permeability μ′ that is sufficient for practical use and has the advantage that change over time is suppressed. EXAMPLES

[0055] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to the following examples.

[0056] <Example 1> First, alloy strip FT-3 (manufactured by Proterial Co., Ltd., magnetostriction constant: λ<1×10) was cast by the single roll method before heat treatment. -6 A 50 mm wide ribbon of the alloy was prepared as a thin alloy ribbon for the magnetic layer. An aramid film (melting point: 278°C, manufactured by Toray Industries, Inc.) with a thickness of 4.4 μm was prepared as an adhesive layer, which was a resin layer to which an epoxy resin (heat-resistant temperature: 200°C, manufactured by Toray Industries, Inc.) was adhered. The adhesive was applied in an amount that would result in a thickness of 10 μm after curing. In order to make it possible to mount the FT-3 ribbon on a magnetic shield lamination machine, a core with a length of 250 m was created. When creating the core, the nanocrystalline material was wound around a core so that the roll surface was on the inner circumference side. Here, the roll surface of the nanocrystalline material refers to the surface of a ribbon of nanocrystalline material cast by the single roll process that comes into contact with the casting roll used to produce the ribbon. After the core was prepared, it was removed from the winding core and heat-treated at 590° C. for 1 hour to obtain an FT-3 nanocrystalline core which was used as a magnetic layer.

[0057] Next, in order to thermocompress the magnetic layer to form a magnetic shielding sheet, the FT-3 nanocrystalline core and the adhesive-attached aramid film prepared above were attached to a laminating device. The laminating device used was a manufacturing device described in JP-A-2007-43077, which has a partial structure shown in FIG. Using this manufacturing equipment, the magnetic layer is made of nanocrystalline material FT-3M, and the protective resin film is made of aramid film, which is the first resin layer formed by laminating a sheet-like epoxy resin, which is the first adhesive layer, and the second adhesive layer is made of sheet-like epoxy resin. The aramid film that would become the second resin layer, formed by laminating a sheet-like epoxy resin, was heated and temporarily bonded with a bonding roll under manufacturing conditions of a heating roll temperature of 60° C. and a line speed of 1 m / min. At this stage, the adhesive has not yet crosslinked or hardened. The laminate that was temporarily heated and pressed was wound continuously around a core to be wound into a long roll. A paper tube was used for the core to ensure heat resistance. Next, in order to crosslink and harden the uncured epoxy adhesive to form an adhesive layer, a heat curing process was performed in a heat treatment furnace at a temperature of 170° C. for a treatment time of 2 hours. The magnetic shield sheet of Example 1 has a layer structure as shown in FIG. After cooling the heat treatment furnace to room temperature (25°C), a magnetic shield sheet of Example 1 was obtained having a cross section as shown in Figure 1 above, including a first resin layer 12, a cured first adhesive layer 14, a magnetic layer 16, a cured second adhesive layer 18, and a second resin layer 20.

[0058] <Comparative Example 1> A 25μm thick polyethylene terephthalate film (PET: melting point: undisclosed: manufactured by Kurabo Industries, Ltd.) was used to form the resin layer, and a polyolefin adhesive (melting point 90℃, manufactured by Kurabo Industries, Ltd.) was used to form the resin layer, forming an adhesive layer with a thickness of 25μm. Although not disclosed in the catalog value, the heat resistance temperature of a typical PET film is less than 200℃. The laminate was heated and pressed by a pressing roll under the production conditions of a heating roll temperature of 110° C. and a line speed of 2.5 m / min. A magnetic shield sheet of Comparative Example 1 was obtained in the same manner as in Example 1, except that the heat curing treatment shown in Example 1 was not carried out.

[0059] Table 1 shows the material configurations and thicknesses of each layer of the magnetic shields of Example 1 and Comparative Example 1.

[0060] [Table 1]

[0061] As is clear from Table 1, the magnetic shield sheet of Example 1 is less than half the thickness of the magnetic shield sheet of Comparative Example 1, and it is therefore possible to reduce the size.

[0062] <Evaluation> <1. Appearance evaluation of heat resistance> The magnetic shield sheets of Example 1 and Comparative Example 1 were evaluated for heat resistance, and the appearance was mainly evaluated before and after the heat resistance test. This evaluation was carried out by a high storage reliability test for 1000 hours at 130° C. That is, the magnetic shielding sheets of Example 1 and Comparative Example 1 were placed in a thermostatic chamber and heated at 130° C. for 1000 hours, and the overall appearance change of the magnetic shielding sheets before and after and the appearance of each layer were observed in detail for evaluation. FIG. 5A is a partially enlarged view of a photograph showing the change in appearance of the magnetic shielding sheet of Example 1 after a high storage reliability test, and FIG. 5B is a partially enlarged view of a photograph showing the change in appearance of the magnetic shielding sheet of Comparative Example 1 after a high storage reliability test. As shown in FIG. 5A, in the magnetic shielding sheet of Example 1, discoloration of the adhesive due to high temperature was observed after the test, but the uniformity of the laminate was maintained overall, and no damage was observed to the nanocrystalline material of the magnetic layer. In contrast, as shown in Fig. 5B, the magnetic shielding sheet of Comparative Example 1 had an overall non-uniform appearance, and it was observed that the nanocrystalline material of the magnetic layer at the edges was exposed due to cracks in the magnetic layer and deformation caused by shrinkage of the PET film, which is the resin layer, and that the nanocrystalline material had fallen off. The solid arrows in Fig. 5B indicate cracks in the magnetic layer, and the dashed arrows indicate the locations where the magnetic layer at the edges has fallen off.

[0063] <2. Magnetic permeability evaluation> The magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 were measured for change in maximum magnetic permeability (μm) during a high storage reliability test. A graph showing the change in maximum magnetic permeability with the passage of heating time is shown in Fig. 6. The horizontal axis of Fig. 6 shows the time elapsed from the start of heating at 130°C, and the vertical axis shows the maximum magnetic permeability. The method for evaluating the maximum magnetic permeability is as follows. (Method of evaluating maximum magnetic permeability) The maximum magnetic permeability (μm) was measured using a Metron Giken direct current magnetic property measuring device, with a sample cut to 15 mm x 200 mm being placed in a single sheet magnetic measurement frame.

[0064] As shown in the graph in FIG. 6, the maximum magnetic permeability μm of the magnetic shielding sheet of Example 1 was equivalent to that before the start of the test even after 1000 hours had passed, and no significant change in the maximum magnetic permeability was observed even during the test under heating conditions. In contrast, it can be seen that the maximum magnetic permeability μm of the magnetic shielding sheet of Comparative Example 1 significantly decreased within 100 hours after the start of the heating test. The decrease in maximum magnetic permeability is considered to be due to the deterioration of the appearance of the nanocrystalline material as the magnetic layer shown in FIG. 5(B). It is evident from the above test results that the magnetic shielding sheet of Example 1 is superior to the magnetic shielding sheet of Comparative Example 1 in both appearance and performance and in heat resistance.

[0065] <Measurement of magnetic permeability by frequency> The magnetic permeability (μ′) of the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 was measured at frequencies of 1 kHz and 10 kHz and compared. The magnetic permeability μ' was measured using a Hewlet Packard impedance analyzer, Model 4194A, with the inductance L measured under the conditions of one sample layer, 10 turns of winding, and an OSC level of 0.5 V, and calculated using the following formula. μ'=(L×average magnetic path length) / (μ0×effective cross-sectional area) The measurement sample was prepared by punching out a magnetic shielding sheet into a ring shape with an outer diameter of φ43 mm and an inner diameter of φ25 mm using a hand press. The measurement results are shown in Figure 7. It was found that the magnetic shield sheet of Example 1 had a higher magnetic permeability μ′ than Comparative Example 1 at frequencies of 1 kHz and 10 kHz that are widely used in practice.

[0066] <Example 2> A magnetic shield sheet of Example 2 was obtained in the same manner as in Example 1, except that the thicknesses of the first resin layer and the second resin layer in Example 1 were each changed to 12 μm.

[0067] <Comparative Example 2> A magnetic shielding sheet of Comparative Example 2 was obtained in the same manner as in Example 1, except that in Example 1, polyphenylene sulfide (PPS) resin (melting point: 260°C to 270°C, manufactured by Toray Industries, Inc.) was used for the first resin layer and the second resin layer, and the thickness was changed to 25 μm, respectively.

[0068] Table 2 shows the material configurations and thicknesses of each layer of the magnetic shields of Example 2 and the reference example.

[0069] [Table 2]

[0070] <Measurement of magnetic permeability by frequency> The magnetic permeability (μ´) of the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2 was measured at frequencies of 1 kHz and 10 kHz, similarly to the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2, and a comparison was made. The results are shown in Figure 8.

[0071] 7 and 8, the frequencies of 1 kHz and 10 kHz for Examples 1 to 2 and Comparative Examples 1 to 2 are as shown below, and it can be seen that the magnetic shielding sheets of the Examples have higher magnetic permeability and exhibit better performance than the magnetic shielding sheets of the Comparative Examples. Permeability of Example 1 (1KHz: 73221.6μ´), (10KHz: 64423.7μ´) Permeability of Comparative Example 1 (1KHz: 54482.7μ´), (10KHz: 42962.9μ´) Permeability of Example 2 (1KHz: 60866.1μ´), (10KHz: 56930.9μ´) Permeability of Comparative Example 2 (1KHz: 56605.7μ´), (10KHz: 43734.6μ´)

[0072] The above evaluation results show that the performance of the magnetic shield sheet is affected by heat resistance, particularly the heat resistance and thickness of the resin layer that functions as a protective layer for the magnetic layer. In other words, it was found that the dimensional stability of each resin layer before and after heating affects the protective performance of the magnetic layer. The resin film constituting the resin layer has different thermal expansion and contraction properties when heated depending on the resin material and thickness, which affects the protective properties of the magnetic layer. By controlling the product of the rate of area change after heat treatment of each resin film relative to before heat treatment and the thickness of the resin layer within a predetermined range, the magnetic permeability of the magnetic shield sheet can be maintained at a high level. For verification purposes, the relationship between the product of the area change rate after heat treatment of each resin film relative to before heat treatment and the thickness of the resin layer, and the magnetic permeability μ' of the resulting magnetic shielding sheet was measured, and the results are shown in FIG. The marks ● in FIG. 9 indicate the results of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 from the left.

[0073] For example, for the aramid resin (thickness: 4.4 μm) used in Example 1, the area change rate measured under the following conditions was 0.997%, or 0.997 × 4.4 = 4.39 (% μm), which achieved 30% μm or less, and also obtained good results in the heat resistance evaluation.

[0074] <Product of area change rate of magnetic shield sheet and thickness of resin sheet, and maximum magnetic permeability at a frequency of 10 kHz> In the magnetic shield sheet, the area change rate of the first resin layer and the second resin layer measured under the following conditions was defined as A%, and the thickness of the first resin layer and the second resin layer was defined as Bμm. The product of A and B (% μm) and the maximum magnetic permeability were measured. The results are shown in Figure 6.

[0075] (Method of measuring area change rate) The resin films constituting the first resin layer and the second resin layer were cut into samples having a size of 100 mm x 100 mm, and the obtained resin film samples were heated in a heat treatment furnace at 200°C for 10 minutes for the aramid resin, which corresponds to the curing temperature of the thermosetting adhesive, and at 150°C for 30 minutes for the other adhesives. The area of ​​the resin film before and after heating was measured, and the area change rate was calculated using the following formula (a). Area change rate (%) = [area of ​​resin film before heating - area of ​​resin film after heating] / area of ​​resin film before heating Formula (a)

[0076] -Method for measuring heat shrinkage- (1) The width and length of the test piece were measured before heating. (2) The test piece was placed in a hot air circulating thermostatic chamber and suspended under a load for a time and temperature condition according to the material of the resin film. (3) After heating, the test piece was cooled to room temperature, and the length of the test piece after the heat treatment was measured at the same portion as that of the test piece before heating that was previously measured. (4) The obtained value was used to calculate the thermal shrinkage rate according to the following formula (b). Heat shrinkage rate (dimensional change rate) (%) = 100 × (Lo-L) / Lo Formula (b) In formula (b), Lo represents the size of the test piece before the heat test, and L represents the size of the test piece after the heat treatment. As described above, the load applied during hanging was adjusted to a level at which the resin film could be hung without being deformed.

[0077] As shown in FIG. 9, when the product (% μm) of A and B is 30% μm or less, a maximum magnetic permeability that poses no practical problems is exhibited at a frequency of 10 kHz. That is, it was confirmed that a magnetic shield sheet with high magnetic permeability can be obtained by reducing the area change rate of the resin layer itself or the laminate, and the thickness of the resin layer. [Explanation of symbols]

[0078] 1 Plastic film roll 2 Heat roll 3. Alloy strip roll 4 Magnetic layer (amorphous alloy ribbon) 5 Winder 6 Resin layer (resin film) 7 Alloy ribbon coil 8. Pressure Roll 9. Magnetic shielding sheet material 10 Magnetic shield sheet 12 First resin layer 14 First adhesive layer 16 Magnetic layer 18 Second adhesive layer 20 Second resin layer 22 Magnetic shield sheet 24 First resin layer 26 First adhesive layer 28 Magnetic layer 30 Second adhesive layer 32 Second resin layer

Claims

1. a laminate having, in this order, a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer; The magnetic layer has a magnetostriction constant λ of 30×10 -6 A magnetic layer having a thickness of 8 μm to 25 μm, comprising the following magnetic material: The first resin layer and the second resin layer are each a resin layer having a thickness of 1 μm to 24 μm and containing a resin having a melting point or sublimation point of 250° C. or higher; The magnetic shield sheet, wherein the first adhesive layer and the second adhesive layer are each an adhesive layer having a thickness of 1 μm to 10 μm and containing an adhesive having a melting point of 150° C. or higher.

2. The magnetic layer is an elongated body having a width of 30 mm to 500 mm, the first resin layer, the first adhesive layer, the second adhesive layer, and the second resin layer each have a width of 300 mm or more; 2. The magnetic shielding sheet according to claim 1, wherein the magnetic layers are arranged in parallel in the longitudinal direction of the elongated body on the surface of the first adhesive layer opposite to the side having the first resin layer.

3. 3. The magnetic shielding sheet according to claim 1, wherein the total thickness of the laminate is 33 μm to 65 μm.

4. 3. The magnetic shielding sheet according to claim 1, which is in a wound roll form.

5. 2. The magnetic shielding sheet according to claim 1, which is a magnetic shielding member obtained by punching the laminate into a desired shape.

6. the first adhesive layer and the second adhesive layer include a thermosetting adhesive; In at least one of the first resin layer and the second resin layer, when an area change rate before and after heating at a temperature at which the thermosetting adhesive is cured is A%, and a thickness of the first resin layer and the second resin layer is B μm, 3. The magnetic shield sheet according to claim 1, wherein the product of A and B is 30%·μm or less. (Method of measuring area change rate) In accordance with JIS C 2151:2019 and ASTM DD1204, a sample of 100 mm x 100 mm was prepared by cutting the resin film constituting the first resin layer and the second resin layer. The obtained resin film sample was heated in a heat treatment furnace under the conditions of 200 ° C. x 10 min or 150 ° C. x 30 min depending on the curing temperature of the thermosetting adhesive, and the thermal shrinkage rate in the width direction and length direction of the resin film before and after heating was measured by the following method. The area was calculated from the product of the obtained width and length, and the area change rate was measured by the following formula (a). Area change rate (%)=absolute value of [area of ​​resin film before heating−area of ​​resin film after heating] / area of ​​resin film before heating Formula (a) -Method of measuring heat shrinkage- (1) Measure the width and length of the test piece before heating. (2) The test piece is placed in a hot air circulating thermostatic chamber and suspended under a load for a time and temperature condition according to the material of the resin film. 3) After heating, cool to room temperature and then measure the length of the heat-treated test piece at the same part as that of the test piece before heating that was previously measured. (4) Using the obtained value, calculate the thermal shrinkage rate according to the following formula (b). Heat shrinkage rate (dimensional change rate) (%) = 100 × (Lo - L) / Lo Formula (b) In formula (b), Lo represents the size of the test piece before the heat test, and L represents the size of the test piece after the heat treatment.

Citation Information

Patent Citations

  • Magnetic shield member

    JP2007317769A